Pengaruh Intensitas Mengakses Instagram Dan TikTok Terhadap Perilaku Imitatif Pada Siswa SMA Al-Irsyad Kota Tegal - Nurcahyawati Lestari; Sarwo Edy; Inas Sany Muyassaroh (Lembaga Pengembangan Kinerja Dosen, 2023)
Social media is a digital platform that facilitates online social activities for users, including communication, interaction, and content creation such as writing, videos, or photos. Information shared on social media can reach a wide audience and be accessed by users globally within a short period, typically within 24 hours. Popular examples of social media platforms include Instagram and TikTok. This research is grounded in New Media theory and Social Learning Theory. These theories align with the hypothesis of the study, particularly in understanding digital data controlled by software, such as social media platforms, and how exposure to social media content can influence behavior, as outlined in the Social Learning Theory. The study focuses on observing imitative behavior among students at Al-Irsyad High School in Tegal City. The research adopts a quantitative approach, specifically descriptive research. Through data analysis, the researchers were able to confirm the hypothesis using the Pearson Product Moment Test or correlation analysis. The findings indicate a positive correlation with a strong degree of association, supporting the hypothesis.